The MI-PHOTOS Project: Understanding the Health and Wellbeing of Rural Historically Marginalized Mothers Through Photovoice. (October 2022) - LeMasters, Katherine H.; Bledsoe, Sarah E.; Brooks, Jada; Chavis, Stephanie; Little, Erica; Pevia, Kim; Daniel, Leah; Jordan, Kiva; Schindler, Ann; Lightfoot, Alexandra F.; ,
Despite the persistent health inequities faced by rural women in the United States, few researchers have partnered with women in rural communities to co-create sustainable change. To fill this gap, Mothers Improving Pregnancy and Postpartum Health Outcomes Through stOry Sharing (MI-PHOTOS) employed a community-based participatory research (CBPR) approach by partnering with mothers, community leaders, and community-based organizations in Robeson County, North Carolina, a rural, racially diverse county. The project's aims were (a) to promote maternal health by listening to mothers' stories of having and raising children in their community and (b) to develop a shared understanding of these mothers' strengths and challenges. MI-PHOTOS utilized photovoice, an exploratory and qualitative CBPR methodology. Grounded theory guided data analysis. During photovoice discussions, conversation focused on maternal experiences and evoked strengths, facilitators, and barriers impacting maternal health. Themes focused on (a) MI-PHOTOS serving as a social support group for the community and family stressors that mothers faced and (b) the necessity of professional support programs. Three overarching findings emerged during this process: (a) MI-PHOTOS as an informal support group, (b) mental health stigmatization, and (c) the need to bridge home visiting programs with peer and confidential therapeutic services. Future work should incorporate mothers' and communities' strengths into program development by drawing on existing home visiting programs, identifying opportunities for peer-support, and creating referral networks for individual, confidential therapeutic services. Through continued community partnership, we can generate fuller understandings of mothers' experiences of having and raising children and ultimately promote health equity among rural mothers.